ANALYSIS OF TRADITIONAL MARKET TRADERS' SURVIVAL STRATEGIES AND SOCIAL, CULTURAL, AND ECONOMIC INTERACTIONS IN THE DIGITAL ERA - Rahma Novita, Dhea; Urrahman, Assyfa; Lubis, Rahmad Ismail; Darmawan, Aldy Fauzan; Hidayat, M Taufik; Desky, Ahmed Fernanda (PERSPEKTIF: Journal of Social and Library Science, 2024)
This research aims to explore the strategies adopted by traditional market traders, particularly the groceries traders at Pajak MMTC Medan City, in responding to the development of the digital market. The approach used in this research is qualitative with data collection methods through in-depth interviews, participatory observation, and documentation studies. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. The research findings show that although Sembako traders in MMTC face challenges from the digital market, they implement various strategies to survive, such as adapting to technology, improving service quality, and strengthening social relationships with consumers. Social interactions rich in local cultural values and mutually beneficial economic relationships are the main factors in maintaining their business continuity. This research is expected to provide deeper insights into the dynamics of traditional markets in the digital era and provide policy recommendations to support the survival of traditional market traders in big cities.